2002
DOI: 10.1258/002221502760238019
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnographic studies in children undergoing adenoidectomy and/or tonsillectomy

Abstract: Forty children (age group four to 12 years) undergoing adenoidectomy and/or tonsillectomy were subjected to pre- and post-operative polysomnography. Thorough clinical evaluation and X-ray soft tissue nasopharynx lateral view was carried out for all the patients. The tonsils were clinically graded from grade I to IV, whereas the adenoids were measured radiographically (using three different measurements) in all children. Thirty out of 40 (75 per cent) children presented with predominant obstructive symptoms, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 10 publications
(23 reference statements)
1
38
0
1
Order By: Relevance
“…As expected, and previously reported [16,17,[19][20][21], marked pre-to-post-surgical changes in respiratory indices during sleep were found. Both the AHI and apnoea index were reduced after T&A, and no longer differed from those of matched controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As expected, and previously reported [16,17,[19][20][21], marked pre-to-post-surgical changes in respiratory indices during sleep were found. Both the AHI and apnoea index were reduced after T&A, and no longer differed from those of matched controls.…”
Section: Discussionsupporting
confidence: 91%
“…Although T&A may not be universally effective in paediatric patients [18], several studies have shown that post-operative recovery from OSA treated with T&A includes normalisation of sleep and respiratory measures [16,17,[19][20][21], and improvements in school performance [2], cognitive function [13,22,23], behaviour [24] and quality of life [25,26].…”
mentioning
confidence: 99%
“…The obstructive apnea index (OAI) was defined as the number of obstructive apneas per hour of sleep. A diagnosis of obstructive sleep apnea was based on PSG in patient with obstructive apnea index >1 and oxygen desaturation Sp O 2 < 92% [10].…”
Section: Methodsmentioning
confidence: 99%
“…Daytime somnolence, fatigue, headaches, poor appetite, short attention span are caused by constant hypoxia and frequent arousals [14,16,19]. Moreover respiratory disorders and frequent infections of upper respiratory tract appear in children with sleep-disordered breathing [1,3,5,6,10]. Sleep apnea may lead to failure to thrive and to physical and mental delay in development, including cognitive disturbances [12,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation